THE NECESSITY OF ISSUING A UNIFIED ID CARD TO CIVIL SERVANTS AND THE PROCEDURES FOR ITS IMPLEMENTATION (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Due to the improvement of information and communication technologies and the rapid pace of digitalization, all sectors, industries, and fields are being digitalized today.